Neisseria meningitidis Uses Sibling Small Regulatory RNAs To Switch from Cataplerotic to Anaplerotic Metabolism - Pannekoek, Yvonne (mBio, 2017)
Neisseria meningitidis (the meningococcus) is primarily a commensal of the human oropharynx that sporadically causes septicemia and meningitis. Meningococci adapt to diverse local host conditions differing in nutrient supply, like the nasopharynx, blood, and cerebrospinal fluid, by changing metabolism and protein repertoire. However, regulatory transcription factors and two-component systems in meningococci involved in adaptation to local nutrient variations are limited. We identified novel sibling small regulatory RNAs (Neisseria metabolic switch regulators [NmsRs]) regulating switches between cataplerotic and anaplerotic metabolism in this pathogen. Overexpression of NmsRs was tolerated in blood but not in cerebrospinal fluid. Expression of six tricarboxylic acid cycle enzymes was downregulated by direct action of NmsRs. Expression of the NmsRs themselves was under the control of the stringent response through the action of RelA. Small sibling regulatory RNAs of meningococci, controlling general metabolic switches, add an exciting twist to their versatile repertoire in bacterial pathogens.